Analysis of Coding Machine Purchase Decisions Using the Analytical Hierarchy Process (AHP) Method - Novrisal, Dimas; Mahmudah, Winni Fazriah (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The increasing public awareness of taking medicines, especially during the COVID-19 pandemic, has made the pharmaceutical industry grow very rapidly. Therefore, the company is trying to increase its production, so it needs to add a coding machine. The choice of machine has a long-term impact because it will be used to assist the production process in the next few years, so it is necessary to use a method that is able to solve problems involving the consideration of company leaders, namely the Analytical Hierarchy Process (AHP) method. The order of priority of the coding machine selection criteria is the ability to print codes (33.6%), maintenance and repair costs (29.6%), the convenience of spare parts, solvents or make-up. and ink (16.2%), price (12.5%), and ease of use (8.1%). Based on the respondent's questionnaire, the order of the best alternative coding machines is Supplier A at 49.12%, Supplier B at 27.28%, and last Supplier C at 23.60%.